Adaptation within embryonic and neonatal heart environment reveals alternative fates for adult c-kit+ cardiac interstitial cells. (31st December 2019) - Wang, Bingyan J.; Alvarez, Roberto; Muliono, Alvin; Sengphanith, Sharon; Monsanto, Megan M.; Weeks, Joi; Sacripanti, Roberto; Sussman, Mark A.
Abstract: Cardiac interstitial cells (CICs) perform essential roles in myocardial biology through preservation of homeostasis as well as response to injury or stress. Studies of murine CIC biology reveal remarkable plasticity in terms of transcriptional reprogramming and ploidy state with important implications for function. Despite over a decade of characterization and in vivo utilization of adult c-Kit + CIC (cCIC), adaptability and functional responses upon delivery to adult mammalian hearts remain poorly understood. Limitations of characterizing cCIC biology following in vitro expansion and adoptive transfer into the adult heart were circumvented by delivery of the donated cells into early cardiogenic environments of embryonic, fetal, and early postnatal developing hearts. These three developmental stages were permissive for retention and persistence, enabling phenotypic evaluation of in vitro expanded cCICs after delivery as well as tissue response following introduction to the host environment. Embryonic blastocyst environment prompted cCIC integration into trophectoderm as well as persistence in amniochorionic membrane. Delivery to fetal myocardium yielded cCIC perivascular localization with fibroblast-like phenotype, similar to cCICs introduced to postnatal P3 heart with persistent cell cycle activity for up to 4 weeks. Fibroblast-like phenotype of exogenously transferred cCICs in fetal and postnatal cardiogenic environments is consistent with inability to contribute directly toward cardiogenesis and lack of functional integration with host myocardium. In contrast, cCICs incorporation into extra-embryonic membranes is consistent with fate of polyploid cells in blastocysts. These findings provide insight into cCIC biology, their inherent predisposition toward fibroblast fates in cardiogenic environments, and remarkable participation in extra-embryonic tissue formation. : Abbreviations: AM amniochorionic membrane AzG Azami Green cCIC c-Kit + cardiac interstitial cell CIC cardiac interstitial cell c-Kit tyrosine-protein kinase kit or CD117 dpi days postinjection E embryonic day # EB embryoid body ECM extracellular matrix ESC embryonic stem cell FUCCI fluorescence ubiquitination-based cell cycle indicators hpi hours postinjection ICM inner cell mass LV left ventricle mKO monomeric Kusabira Orange P postnatal day # SMA smooth muscle actin TE trophectoderm TenC tenascin C TUNEL terminal deoxynucleotidyl transferase dUTP nick end labeling Vim vimentin Abstract : Adult c-Kit + cardiac interstitial cells (cCICs) were assessed for retention, persistence, and phenotypic characteristics at three developmental stages: embryonic (E3.5), fetal (E15.5), and neonatal hearts (P3). cCICs delivered into E3.5 subsequently integrated into extra-embryonic membranes. cCICs delivered into E15.5 and P3 exhibited a fibroblast-like phenotype, with persistence and cell cycle activity up to 28 days in P3 hearts.